Islamic Worldview as a Model for De-Westernising Journalism Studies and Profession - Ibrahim, Basyouni (Javnost-The Public, 2022)
Despite the various attempts to de-Westernise journalism studies and profession, the dominance of Western theories and practices remains absolute. This article seeks to develop a hybrid Islamic/Western worldview that represents a comprehensive, flexible and multicultural paradigm that emphasises sharing rather than imposing one’s heritage and view. The article particularly reflects on resolving the existing ontological, epistemological and methodological issues as a crucial task in overcoming obstacles and stagnation related to the hybridisation of theory-building efforts. This article demonstrates how the proposed normative paradigm can be grounded in the realistic context of journalistic practice by examining two research issues: media and democratisation and the globalisation of journalism ethics.